Aplikasi Analisis (Path Analysis) Berdasarkan Urutan Penempatan Variabel Dalam Penelitian - Sudaryono -- (Jurnal Pendidikan dan Kebudayaan, 2011)
In quantitative research there is a method called path analysis that examines chronological cause and effect among variables. Since cause and effect play an important role guideline in which the analysis is applied, showing the path analysis components with applied corelation analysis among variables based on their chronological effect would give description how important the path analysis is to be acknowledged by reserachers. It’s objective is to examine direct and indirect effect a set of variables, as the cause variables towards other variables as the effect variables. The purpose this article is to enrich research methods that may be used to analysis the relation patern among the variables. Problem formulation of this article focuses on the question is path analysis effective for educational research and can it answer issues in educational research. Literature reviews and researchs using path analysis reveal that it is very effective and needs to be developed in educational research.